A new degree of complexi(n)ty in the regulation of GLUT4 trafficking. Issue 7 (16th April 2021) - Bertrand, Luc; De Loof, Marine; Beauloye, Christophe; Horman, Sandrine; Bultot, Laurent
Abstract : Loss of the insulin-stimulated glucose uptake in muscle is a crucial event participating in the defect of whole-body metabolism in type 2 diabetes. Therefore, identification by Pavarotti et al. (Biochem. J (2021) 478 (2): 407–422) of complexin-2 as an important contributor to glucose transporter 4 (GLUT4) translocation to muscle cell plasma membrane upon insulin stimulation is essential. The present commentary discusses the biological importance of the findings and proposes future challenges and opportunities.